Nutritional Intervention Incorporating Expedited 10 g Protein Counter (EP-10) to Improve the Albumin and Transferrin of Chronic Hemodialysis Patients. (22nd October 2012) - Lim, Su-Lin; Lye, Jamie
Abstract : Objective . The expedited 10 g protein counter (EP-10) is a quick and valid clinical tool for dietary protein quantification. This study aims to assess the clinical effectiveness of the EP-10 in improving serum albumin and transferrin in chronic hemodialysis patients. Methods . Forty-five patients with low serum albumin (<38 g/L) were enrolled in this study. Parameters measured included dry weight, height, dietary intake, and levels of serum albumin, transferrin, potassium, phosphate, and kinetic modeling (Kt/V). The nutritional intervention incorporated the EP-10 in two ways (1) to quantify protein intake of patients and (2) to educate patients to meet their protein requirements. Mean values of the nutritional parameters before and after intervention were compared using paired t -test. Results . Three months after nutritional intervention, mean albumin levels increased significantly from 32.2 ± 4.8 g/L to 37.0 ± 3.2 g/L( P < 0.001 ) . Thirty-eight (84%) patients showed an increase in albumin levels, while two (4%) maintained their levels. Of the thirty-six (80%) patients with low transferrin levels (<200 mg/dL), 28 (78%) had an increase and two maintained their levels after intervention. Mean transferrin levels increased significantly from 169.4 ± 39.9 mg/dL to 180.9 ± 38.1 mg/dL( P < 0.05 ) . Conclusion . Nutritional intervention incorporating the EP-10 method is able to make significant improvements to albumin and transferrin levels of chronic hemodialysis patients.